2009
DOI: 10.1029/2008wr006955
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of wetlands: Quantifying trade‐offs between flood risks, recreation, and biodiversity conservation

Abstract: [1] This paper employs a simple choice experiment to estimate the value of management options for the Bobrek wetland in Poland. The local public's valuation of several wetland management attributes, including flood risk reduction, biodiversity conservation and improvement of recreational access, are investigated. A latent class model is estimated to account for heterogeneity in the wetland management choices of the local public. The results reveal that there is considerable heterogeneity among the local public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 70 publications
4
31
0
Order By: Relevance
“…Development processes in river valleys intensified, particularly in the 18 th century, as industrialisation and urbanisation progressed rapidly. Many urban and industrial centres were located in river valleys and the towns that had existed there for hundreds of years 1 Faculty of Earth Sciences, University of Silesia, ul. Będzińska 60, 41-200 Sosnowiec, Poland * Corresponding author: mrz@wnoz.us.edu.pl expanded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development processes in river valleys intensified, particularly in the 18 th century, as industrialisation and urbanisation progressed rapidly. Many urban and industrial centres were located in river valleys and the towns that had existed there for hundreds of years 1 Faculty of Earth Sciences, University of Silesia, ul. Będzińska 60, 41-200 Sosnowiec, Poland * Corresponding author: mrz@wnoz.us.edu.pl expanded.…”
Section: Introductionmentioning
confidence: 99%
“…As a result such valleys started to function as axes of national economies. While taking advantage of the benefits provided by rivers and their valleys both in the past and in the present, humans have always been aware of the great dangers associated with flowing water [1]. Since the times of early settlements built on river banks, hydraulic engineering structures have been constructed to act as protection from the devastating effects of floods [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Although Finland regularly encounters floods, they are considerably less dramatic compared to floods further south in Europe, where the loss of life and substantial economic damage has occurred several times during the recent decades (Hajat et al 2005). For example, in the study by Birol et al (2009) (Farber et al 2002). This difference is apparently recognized by people who intrinsically value environmental and natural resources highly.…”
Section: Discussionmentioning
confidence: 88%
“…In the case of Flanders we found that 35% of the remaining wetlands have no spatial planning or protection status, while 49,000 ha (33%) of potential wetlands lack investments for restoration despite their appropriate status (see Appendix 8). As was demonstrated in many other countries (e.g., Birol et al 2009, Buijs 2009, Scholte et al 2016) flood protection is more widely accepted as a motivation for wetland restoration than biodiversity conservation. In the Flemish floodplains this is demonstrated by the still dominant, more or less intensive agricultural use with fertilization and active drainage of wet grasslands.…”
Section: Wetland Restoration and Biodiversity Conservationmentioning
confidence: 97%